2010
DOI: 10.1038/modpathol.2010.48
|View full text |Cite
|
Sign up to set email alerts
|

CD20, AIF-1, and TGF-β in graft-versus-host disease: a study of mRNA expression in histologically matched skin biopsies

Abstract: Graft-versus-host disease is the leading cause of non-relapse mortality after allogeneic bone marrow transplantation. The cell-mediated immune mechanisms that underlie the pathogenesis of graft-versus-host disease remain unclear. In this study, 47 skin biopsies representing graft-versus-host disease grades 0–III, lichenoid, and sclerodermoid were included from 31 allogeneic bone marrow transplantation recipients. RNA from paraffin-embedded tissue was harvested. Transcript levels of the following markers were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 37 publications
4
13
0
Order By: Relevance
“…TGFβ mRNA transcripts were found to be elevated in skin biopsies of patients experiencing cutaneous GVHD (10). Additionally, high dose irradiation can stimulate overproduction of TGFβ1 in the human lung (11).…”
Section: Regulation Of Tgfβ Post-hsctmentioning
confidence: 99%
“…TGFβ mRNA transcripts were found to be elevated in skin biopsies of patients experiencing cutaneous GVHD (10). Additionally, high dose irradiation can stimulate overproduction of TGFβ1 in the human lung (11).…”
Section: Regulation Of Tgfβ Post-hsctmentioning
confidence: 99%
“…86 In a small study, evaluation of RNA from paraffinembedded tissues harvested from sclerotic skin revealed increased transcript levels of allograft inflammatory factor-1 (AIF-1) and transforming growth factor-beta, whereas lesions resembling lichen planus contained higher levels of CD20 1 cells. 96 …”
Section: Sclerotic Manifestations Of Chronic Gvhdmentioning
confidence: 97%
“…2 The onset of this posttransplantation complication, termed acute GVHD, is characterized by cutaneous eruptions, rash, and purpuric lesions in the skin along with infiltrates of T cells into the epidermis. 3 Pathologic changes consistent with an acute inflammatory response can also be detected in the gastrointestinal tract and the liver during acute GVHD.…”
mentioning
confidence: 99%
“…Recent studies suggest that both acute and chronic GVHD have distinct cytokine responses. 3 In this regard, recent studies also suggest that the effector T cells shift from a type 1 profile to a type 2 profile during the transition from acute to chronic GVHD. 8 This transition appears to be the result of a breakdown in self-tolerance.…”
mentioning
confidence: 99%
See 1 more Smart Citation